Downhill turn techniques and associated physical characteristics in cross-country skiers - Bucher Sandbakk, S.; Supej, M.; Sandbakk, O.; Holmberg, H. C. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Three dominant techniques are used for downhill turning in cross-country skiing. In this study, kinematic, kinetic, and temporal characteristics of these techniques are described and related to skier strength and power. Twelve elite female cross-country skiers performed six consecutive turns of standardized geometry while being monitored by a Global Navigation Satellite System. Overall time was used as an indicator of performance. Skiing and turning parameters were determined from skier trajectories; the proportional use of each technique was determined from video analysis. Leg strength and power were determined by isometric squats and countermovement jumps on a force plate. Snow plowing, parallel skidding, and step turning were utilized for all turns. Faster skiers employed less snow plowing and more step turning, more rapid deceleration and earlier initiation of step turning at higher speed (r = 0.80-0.93; all P < 0.01). Better performance was significantly correlated to higher mean speed and shorter trajectory (r = 0.99/0.65; both P < 0.05) and to countermovement jump characteristics of peak force, time to peak force, and rate of force development (r = -0.71/0.78/-0.83; all P < 0.05). In conclusion, faster skiers used step turning to a greater extent and exhibited higher maximal leg power, which enabled them to combine high speeds with shorter trajectories during turns.